The Effect of Battery Settings and Fan Parameters on the Performance of the Lithium-Ion Battery Thermal Management System in a Circular Configuration - Luthfi, Muhammad; Ghozali, Muhamad; Kurniawan, Yudhy (Universitas Pendidikan Ganesha, 2024)
This study examines the performance of a thermal management system for 18650 lithium-ion batteries using a circular placement configuration and a forward-curved fan. Experiments were conducted with variations in fan speed, the number of fan blades, and battery positioning (aligned or zigzag) to observe their effects on temperature and temperature distribution during the battery discharge process. The results showed that increasing fan speed significantly reduced battery temperature to around 30-33°C and improved temperature distribution uniformity with a standard deviation ranging from 0.5 to 1.21°C. Meanwhile, variations in the number of fan blades and battery positioning had an insignificant impact on temperature reduction but did influence temperature distribution uniformity, with the lowest standard deviation of 0.5-0.6°C observed in the three-blade variation. The zigzag positioning provided a more uniform temperature distribution compared to the aligned positioning, with a standard deviation of 0.51-0.97°C